2013
DOI: 10.1038/jcbfm.2013.29
|View full text |Cite
|
Sign up to set email alerts
|

Partial Volume Correction using Structural–Functional Synergistic Resolution Recovery: Comparison with Geometric Transfer Matrix Method

Abstract: We validated the use of a novel image-based method for partial volume correction (PVC), structural-functional synergistic resolution recovery (SFS-RR) for the accurate quantification of dopamine synthesis capacity measured using [ 18 F]DOPA positron emission tomography. The bias and reliability of SFS-RR were compared with the geometric transfer matrix (GTM) method. Both methodologies were applied to the parametric maps of [ 18 F]DOPA utilization rates (k i cer ). Validation was first performed by measuring re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Both tumor macroparameters V T and BP ND , and microparameter K 1 significantly changed after application of PVC. This corresponds with results from applications of PVC in brain dynamic PET studies, where similar increases in kinetic parameter estimations have been observed when applying PVC in the case of activity spill-out [19–21, 31]. Interestingly, the effect of PVC on kinetic parameter estimates was poorly (albeit significantly) correlated with its effect on simplified measures.…”
Section: Discussionsupporting
confidence: 85%
“…Both tumor macroparameters V T and BP ND , and microparameter K 1 significantly changed after application of PVC. This corresponds with results from applications of PVC in brain dynamic PET studies, where similar increases in kinetic parameter estimations have been observed when applying PVC in the case of activity spill-out [19–21, 31]. Interestingly, the effect of PVC on kinetic parameter estimates was poorly (albeit significantly) correlated with its effect on simplified measures.…”
Section: Discussionsupporting
confidence: 85%
“…In our implementation, a brain tissue mask is generated based on FreeSurfer segmentation, a CSF dilution factor is calculated for each region, and the raw time activity curve for each region is corrected by this dilution factor before BP ND is calculated. The second method is based on computation of the regional spread function (RSF) (Rousset et al, 2008; Rousset et al, 1998), which has also been extensively applied in PET imaging analysis (Kim et al, 2013; Kuhn et al, 2014; Le Pogam et al, 2011). Our implementation of RSF PVC also included additional ROIs outside the brain (hence, not defined by FreeSurfer) to account for tracer uptake in non-brain tissue.…”
Section: Methodsmentioning
confidence: 99%
“…These become important for structures two to three times smaller than the resolution of the scanner. 60,61 These effects include loss of signal in affected regions as well as spill-over from neighbouring structures. Where there is a loss of volume in a region, as there is in cortical regions in schizophrenia, 62 this could bias group comparisons.…”
Section: General Methodological Considerationsmentioning
confidence: 99%